Isolasi dan Karakterisasi Bakteri pada Pasir Sarang dan Cangkang Telur Penyu Lekang (Lepidochelys olivaceae L.) yang Menetas dan Gagal Menetas - Osmia Hidayat; Fuji Astuti Febria; Nasril Nasir (Jurnal Biologi Universitas Andalas, 2014)
Isolation and Characterization of Bacteria from nest sand and egg shell of Olive Ridley (Lepidochelys olivacea L.) which hatched and failed to hatch in Pariaman turtle conservation site, West Sumatra were conducted from December 2012 to September 2013 in Microbiology Laboratory, Andalas University and Laboratory of Provincial Health Department, West Sumatra. The aim of this study was to identify species of bacteria found at egg shells and nest sand of Olive Ridley in Pariaman. The result found 4 species of bacteria: Bacillus cereus and Klebsiella sp. from sand nest that hatched; while Bacillus cereus, Klebsiella sp. and Shigella sp. were identified from sand nest that failed to hatch. Bacteria isolates from egg shell that hatched were identified as Bacillus cereus, Klebsiella sp. While Bacillus cereus, Klebsiella sp., Salmonella sp. and Shigella sp. were identified from egg shell that failed to hatch. Keywords: isolation, bacteria, nest sand, egg shell, Olive Ridley